Crime and Residential Choice: A Neighborhood Level Analysis of the Impact of Crime on Housing Prices - Tita, George E. (Journal of quantitative criminology, 2006)
Crime serves as an important catalyst for change in the socio-economic composition of communities. While such change occurs over a long period of time, crime is capitalized into local housing markets quickly and thus provides an early indicator of neighborhood transition. Using hedonic regression, we quantify this “intangible cost” of crime and extend the crime-housing price literature in several important ways. First, we disaggregate crime to the census tract level. Second, using longitudinal data, we examine changes in crime in addition to the neighborhood levels of crime. Third, we differentiate between the effects of property crime and violent crime. Fourth, we also disaggregate our sample into groups based on per capita income of the census tract. Finally, we show that it is vital to account for the measurement error that is endemic in reported crime statistics. We address this with an instrumental variable approach. Our results indicate that the average impacts of crime rates on house prices are misleading. We find that crime is capitalized at different rates for poor, middle class and wealthy neighborhoods and that violent crime imparts the greatest cost.